Ketersediaan Modal Dan Pengaruhnya Terhadap Pendapatan Usahatani Padi Sawah di Kecamatan Tilongkabila Kabupaten Bone Bolango - Risti Fadilah Umar; Yuliana Bakari; Supriyo Imran; Muhammad Zubair Hippy (Universitas Medan Area, 2023)
Capital has an important role in farming, because making production more efficient and increasing income effectiveness. This research aims to determine the source and availability of capital as well as the effect of the source of capital on the income of rice field farming in the Tilongkabila Subdistrict, Bone Bolango Regency. Samples are determined using the Nomogram Harry King for as many as 120 respondents, using the non-probability sampling method by accidental sampling. Research data types and sources are primary and secondary. The method of analyzed descriptive and multiple linear regression analysis. Research results show that, 93% of the availability of rice field farming capital in the Tilongkabila Subdistrict, Bone Bolango Regency, can be fulfilled Furthermore, the research also indicates that the source of personal capital had no positive effect on rice field farming income. It is similar to the source of loan capital having no positive impact on rice field farming income. The R square results, the variables owncapital and loan capital have a proportion of influence on rice farming income in Tilongkabila District of 6,9%, while the remaining 93,1% is influenced by other variables that are not in the multiple linear regression model.